Preparing for design-build projects : a primer for owners, engineers, and contractors - Gransberg, Douglas D. (American Society of Civil Engineers, 2006)
Foreword by Michael C. Loulakis, Esq. For nearly two decades, design-build (DB) contracting has become increasingly the method of choice in public and private construction projects. Many designers and builders are now drawn to design-build projects and must alter their business practices to accommodate the changed relationships within DB contracts. Preparing for Design-Build Projects: A Primer for Owners, Engineers, and Contractors is a professional reference that covers the basics of developing a design-build project. The authors focus on learning modules that break down the decision-making process and reassemble it as a straightforward method for DB projects from the owner's standpoint. This book acts as a timely guide on developing DB requests for qualification and requests for proposals. It also assists the reader in interpreting these documents in order to prepare a responsive DB proposal or to evaluate a series of proposals and make a source selection decision.
Keywords: Building -- Superintendence.; Buildings -- Specifications.; Contractors' operations.; elektronické knihy; electronic books